(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2021)
Corn waste agricultural by-product that can be used for animal feed at Nusa Tenggara Timur (NTT) has a longer dry climate than the rainy ones, caused difficulties in terms of feeding. Farmers utilize corn waste as feed resource. This study was carried out to determine the potential corn waste and evaluate the potential capacities of livestock from corn waste as animal feed. The data was obtained from farmer group, collected during December 2019 to April 2020 in Oeteta Village, Kupang Timur - NTT. The data of corn waste material production included corn straw (stalks and leaves), corn cob, and corn husk in 7 hectares area. Data were collected by using the survey with simple random sampling for estimation of carrying capacity value. The results showed that the fresh corn waste production on the land area of 7 hectares in the Oeteta village were fresh corn straw (451,101 kg year-1), corn cob (65,225.58 kg year-1), corn husk (10,870.86 kg year-1), and total 527,197.44 kg year-1 of corn waste production. Utilization of corn waste as feed stock with the use of 30% in the ration generated a carrying capacity of 352 cattle and 2,464 goats respectively, have a carrying capacity 352 head of beef cattle and 2,464 head of goats, whereas if the use was 40% in the ration, the carrying capacity was 264 cattle and 1,851 goats. It could be concluded that the feed from corn waste available in Oeteta Village, Kupang Regency, NTT, which is 7 ha of area have sufficient carrying capacity for livestock. Key words: carrying capacity, corn waste, Oeteta Nusa Tenggara Timur